Digital Colonialism in AI-Enhanced Sustainability Education: A Decolonial Systematic Review - Matthew Sauber (Journal of Education for Sustainable Development Studies, 2026)
As artificial intelligence reshapes higher education globally, its integration into sustainability programs raises urgent questions about equity, epistemological justice, and the reproduction of colonial power structures through technological systems. Education for Sustainable Development (ESD) is premised on inclusive, justice-oriented pedagogy, yet the AI tools increasingly deployed in these programs originate predominantly from the Global North and embed Western epistemological assumptions. This study investigates how AI integration in higher education sustainability programs operates as a form of digital colonialism, creating systematic inequities that contradict ESD’s foundational commitments. We conducted a decolonial systematic review synthesizing 61 empirical studies identified through structured searches of ERIC, Scopus, Web of Science, IEEE Xplore, Education Source, and PsycINFO databases (2019-2024). Studies were selected using explicit inclusion and exclusion criteria, and findings were analyzed through a decolonial analytical framework informed by Santos’s epistemologies of the South and Mignolo’s concept of epistemic disobedience. Our findings expose three mechanisms of educational imperialism: institutional stratification, where elite universities achieve 84% AI implementation success versus 42% for under-resourced institutions serving marginalized communities; algorithmic violence, manifesting in 34% lower completion rates for students from formerly colonized regions; and epistemological erasure, as AI systems privilege Western scientific paradigms over traditional ecological knowledge. We reconceptualize the TPACK-AI framework as a tool for technological sovereignty, incorporating decolonial pedagogies, algorithmic resistance, and community-centered design. Without systematic decolonization of educational technology, AI integration risks accelerating the exclusion of Indigenous, Black, and Global South voices from environmental leadership. This research contributes strategies for institutions to resist digital colonialism through South-South cooperation, community-controlled technologies, and pedagogies that center rather than silence marginalized ways of knowing.